Buccal space tumours. Issue 2 (April 2019) - Hasan, Zubair; Tan, Darius; Buchanan, Malcolm; Palme, Carsten; Riffat, Faruque
Abstract: Objective: To review the available literature as it pertains to the buccal space with a specific focus on the pathologies encountered within this space. Clinical presentation, investigations, and surgical approaches to the region are also reviewed. Methods: A systematic review of the available literature was performed on buccal space tumours from 1980 to 2017. Data was extracted on clinical presentation, investigations and surgical approaches to the buccal space. The pathologies encountered in the buccal space were reviewed and presented. Results: Forty-nine unique articles were reviewed, with a total 217 patients. The age of the patients ranged from 0 to 83 with a mean age of 45.8. A total of 51 pathologies were reported. The majority of these were vascular and salivary gland pathologies. The majority of salivary gland neoplasms were malignant. However a wide variety of benign and malignant soft tissue tumours were also reported to occur in this region. Conclusions: The buccal space is a small and complex region with a variety of pathologies occurring within it. This review clarifies the differential diagnosis of a mass which presents in this area and the pathologies which occur within it.